Preparation and Characterization of Dutasteride Nanoparticles as Oral Fast-Dissolving Film - Kadhum, Rusul W.; Abd-Alhammid , Shaimaa N. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Dutasteride, is a drug whose mechanism of action is inhibition of the enzyme 5-alpha reductase. It has been approved for use in the treatment of benign prostatic hyperplasia. Dutasteride has low solubility and high permeability, which classifies it as Biopharmaceutics classification system class II, according to the Biopharmaceutics Classification System. It has a water solubility of only 0.038 ng/mL and a slow dissolving rate, resulting in its exclusive availability in the market as a formulation contained within soft gelatin capsules. Objective: The aim of this study involves two parts. First, is the enhancement of dutasteride dissolution rate, by the creation of dutasteride nanosuspension, and second is the enhancement of patient compliance by the transformation of this nanosuspension to oral fast-dissolving film, which is characterized by its fast disintegration, stability, and ease of administration. Methods: The solvent anti/solvent precipitation method was used to formulate dutasteride nanosuspension. In addition, dutasteride nanoparticles oral fast dissolving films were prepared by using the solvent casting method. To compare the in vitro release patterns of pure dutasteride film and selected dutasteride nanoparticles film, the statistical analysis for the dissolution investigation was conducted using the model-independent technique (employing similarity factor f2) utilizing a DD solver. The selected dutasteride nanoparticle film was supposed to be the test material, while the pure dutasteride film was supposed to serve as the reference. Results: dutasteride nanosuspension demonstrated a high enhancement of the dissolution rate. In addition, the prepared dutasteride nanoparticles oral fast-dissolving film exhibited a further increase in the rate of dissolution and fast disintegration, and the administration is easy, all of these properties making it a promising dosage form. Conclusion: Nanosuspension is an excellent approach for enhancing the solubility, dissolution rate, and effectiveness of drugs with limited aqueous solubility such as dutasteride. In addition, the oral fast-dissolving film can be considered a promising dosage form that will increase patient compliance due to its high dissolution rate, fast disintegration, and easy administration.